Peaceful Coexistence between Muslims and Others in Fallujah During the Ottoman and Royal Eras (Islamic Sciences Journal, 2023)
The importance of this topic comes from its documents of the issue of peaceful coexistence in Islamic thought, and on the other hand it tracks this coexistence in important historical stages that passed over Iraq in general and the city of Fallujah in particular during the historical period in the Ottoman and Royal Eras. The research also adopted the historical documentation of the manifestations of this coexistence between Muslims and other minorities. Religion and nationalism, the Jews lived in the city of Fallujah in peace and harmony, and they had human, economic and social ties and bonds.Fallujah embraced the Christians who came outside and inside Iraq, and they linked with their Muslim brothers (in Fallujah) with common interests and distinct human relations.The Righteous Mandaeans in Iraq have a long history, and they came to Fallujah, and they merged with its people, and a large part of them entered the Islamic religion.
Keywords: Peaceful Coexistence, Fallujah, the Ottoman era, the Monarchy, the Christians.